ANALISIS PERUBAHAN ZONA NILAI TANAH KAWASAN PERMUKIMAN AKIBAT PERUBAHAN LAHAN PERMUKIMAN DI KECAMATAN REMBANG, KABUPATEN REMBANG TAHUN 2019-2023 - Wijaya, Arwan Putra; Praptaningtyas, Berliana Dwi; Qoyimah, Shofiyatul (JURNAL GEOGRAFI, 2024)
The Rembang Subdistrict is experiencing continuous population and economic growth each year, posing significant challenges related to the availability of land for settlements. The increase in population, supported by adequate public facilities and accessibility, serves as the primary driver behind the development of settlements from 2019 to 2023. The noticeable impact of the increasing demand is reflected in the rise of land values in the Rembang Subdistrict Residential Area. This research aims to understand changes in the use of residential land and land values during this period using overlay techniques. Regression curve estimation analysis was conducted to evaluate the influence of changes in land area, accessibility, and public facilities on land values. The research findings indicate a change in residential land use of approximately 1,05071 km2 from 2019 to 2023. The Map of Changes in Land Values in the Rembang Subdistrict Residential Area identifies the highest value in Zone 43 at Rp.8,734,000 and the lowest in Zone 103 at Rp.19,000. The most influential factor in changing land values is the distance from the zone to the Rembang Market. Overall, the results of the nearest neighbor analysis (ANN) show a clustered settlement distribution pattern with a T or NNR scale of 0.0824197